Peran Administrasi Dan Manajemen Dalam Pendidikan Agama Kristen Di Sekolah Dasar - Tan, Juan Ananta; Agata, Krinanda; Sabadnugroho, Samuel; Liantoro, Liantoro; Soenjaya, Lindawaty (Indonesian Journal of Religious, 2023)
Effective teachers in primary schools face difficulties due to a lack of responsibility and a lack of application of Christian values, which serve as the foundation for their leadership. The role of administration and management in Christian Religious Education (CRE) in primary schools is very important in fostering the spiritual and moral development of students. This abstract explores the important functions played by administrators and managers in facilitating PAK programs and ensuring their effectiveness in the basic education environment. Administrators and managers collaborate to design a PAK curriculum that aligns with the mission and values of the educational institution, while meeting the needs and expectations of students and their families. This includes selecting appropriate textbooks, teaching materials, and resources. Selecting qualified educators and providing them with ongoing training and support is an important administrative function. Teachers who are skilled and experienced in Christian theology and pedagogical strategies can provide meaningful religious education for students. The role of administration and management in Christian religious education in primary schools is multifaceted and is very important for student development in an educational context.   Tantangan guru yang efektif di sekolah dasar terletak pada tidak adanya akuntabilitas dan kurangnya penerapan nilai-nilai kristiani, yang memandu kepemimpinan guru di sekolah dasar. Peran administrasi dan manajemen dalam Pendidikan Agama Kristen (PAK) di sekolah dasar sangat penting dalam membina perkembangan spiritual dan moral para siswa. Abstrak ini mengeksplorasi fungsi-fungsi penting yang dimainkan oleh para administrator dan manajer dalam memfasilitasi program-program PAK dan memastikan keefektifannya di lingkungan pendidikan dasar. Administrator dan manajer berkolaborasi untuk merancang kurikulum PAK yang selaras dengan misi dan nilai-nilai lembaga pendidikan, sekaligus memenuhi kebutuhan dan harapan siswa dan keluarga mereka. Hal ini termasuk memilih buku pelajaran, bahan ajar, dan sumber daya yang sesuai. Memilih pendidik yang berkualitas dan memberi mereka pelatihan dan dukungan yang berkelanjutan adalah fungsi administrasi yang penting. Guru-guru yang terampil dan berpengalaman dalam teologi Kristen dan strategi pedagogis dapat memberikan pendidikan agama yang bermakna bagi para siswa. Peran administrasi dan manajemen dalam Pendidikan Agama Kristen di sekolah dasar memiliki banyak segi dan sangat penting bagi perkembangan siswa dalam konteks pendidikan.